Democratic Evaluation (Better Evaluation)
Democratic Evaluation is an approach where the aim of the evaluation i s to serve the whole community. This allows people to be informed of w hat others are doing and sees the evaluator as someone who brokers the process. It generally focuses on inclusive practices which foster par ticipation and collaboration. However it is also used as a means of en suring public accountability and transparency.